Architectural Response - Ability - Wolf Von Eckardt (Oz, 1985)
It has become fashionable among architects and architecture students to be anti-modern, or 'post-modern' as the code name has it. It is a reactionary sentiment which does nothing to advance the essential social purposes of architecture…